Perception of Political Science Education Teachers Towards Professional Development (Orchid Academia Siraha, 2022)
This paper aims to analyse how the Political Science Education teachers perceive professional development. Similarly this study has focused on the different experience in teaching professionalism and its influence in teaching-learning process. but, in here, teachers perceived the teaching profession as a well respected one and looked at it as a low grade profession and they are only teaching, till they get an opportunity for a more lucrative job. Participants emphasised to make common consensus that Society plays a crucial role in steering reinforcement from Society towards the profession; it motivates the teachers to develop themselves professionally. There are always the few people that don't and will not see the profession as a respectable one but teachers required to look past these, and try to understand the gravity of the responsibility entrusted upon them.